History of the Anales de la Facultad de Medicina (1918 - 1998) - Piscoya Arbañil, José (1998)
The aim of this paper is to show the development of the journal Annals of the Faculty of Medicine, the oldest Peruvian medical journal published nowadays. In order to accomplish this goal we reviewed the past volumes that are part of the invaluable collection of the San Fernando Faculty of Medicine Museum of Health Sciences. Its pages are witness of the development experienced during the past 80 years of biomedical science, as well as the development of Public Health, Medical Education, Medical Ethics, and History of Medicine, therefore the Peruvian Medical School. Since its re-launching in 1995, this journal reflects the professional quality of a number of generations of Peruvian physicians and is one of the most constant periodical journal and aims to take a place that used to have in the past, thus the best Peruvian journal.